SV2 acts via Presynaptic Calcium to Regulate Neurotransmitter Release - Wan, Qun-Fang (2010)
Synaptic Vesicle 2 (SV2) proteins, critical for proper nervous system function, are implicated in human epilepsy, yet, little is known about their function. We demonstrate for the first time, using direct approaches, that loss of the major SV2 isoform in a central nervous system nerve terminal is associated with an elevation in both resting and evoked presynaptic Ca(2+) signals. This increase is essential for the expression of the SV2B(−/−)secretory phenotype, characterized by changes in synaptic vesicle dynamics, synaptic plasticity, and synaptic strength. Short-term reproduction of the Ca(2+) phenotype in wild-type nerve terminals reproduces almost all aspects of the SV2B(−/−) phenotype, while rescue of the Ca(2+) phenotype in SV2B(−/−) neurons relieves every facet of the SV2B(−/−) secretory phenotype. Thus, SV2 controls key aspects of synaptic functionality via its ability to regulate presynaptic Ca(2+), suggesting a potential new target for therapeutic intervention in the treatment of epilepsy.